Parental perception of facilitators and barriers to health among young children with down syndrome: a qualitative study - Caldwell, Angela R.; Kim, Yeook; Alshahwan, Nada; Vellody, Kishore; Bendixen, Roxanna M.; Renz, Kayley; Duong, Tiffany; Dodd, Judith; Terhorst, Lauren; Must, Aviva (Frontiers in Pediatrics, 2023)
Background Despite high rates of obesity and weight-related conditions observed in children with Down syndrome, little is known about how to prevent these conditions. Purpose The purpose of this study was to identify parent-perceived facilitators and barriers to health for toddlers (12–36 months old) with Down syndrome. Materials and methods We conducted in-depth, semi-structured interviews with the mothers of 25 toddlers with Down syndrome. All interviews were conducted using Zoom Video Technology, audio recorded and transcribed before being coded in NVivo software using a structured protocol. Thematic analysis was used to identify themes in perceived facilitators and barriers to health at the level of the child, family, and community. Data were triangulated using reflective journaling, video review of child meals, and member-checking techniques. Results We identified unique themes for facilitators (on the move and sound sleep) and barriers (co-occurring conditions and eating behaviors) at the level of the child. At the level of the family and community, overarching themes that were viewed as either a facilitator or barrier, depending on the context, were identified (role models matter, time is critical, the importance of place, and social support). Conclusion These themes can help clinicians and researchers tailor their health promotion interventions to meet the unique needs of children with Down syndrome by using strength-based approaches and providing families with the tools to overcome barriers.